New Managerialism in Education - Lynch, Kathleen. author. aut Link
VIII, 265 p.
Keywords: This book examines the impact of neo-liberal reform on the traditional caring ethos of public services such as education, exploring how these reforms influence the appointment and experiences of senior management across the education sector.